MANAGEMENT TRAINING IN IRAQ BETWEEN REALITY AND ASPIRATION - الدوري, حسين (Dirasat in Economics and Business, 1976)
This study aim to give a complete presentation of the management training activity and its objectives. In addition, it presents the planning method used for management trainning, taking into consideration the importance of management activity in developing countries.